2009
DOI: 10.1097/med.0b013e328332b7f2
|View full text |Cite
|
Sign up to set email alerts
|

The role of assisted reproductive technology in the management of recurrent pregnancy loss

Abstract: Through the screening of embryos for abnormality in chromosome number or structure and selecting only normal embryos for transfer, PGS was envisioned and applied as a therapeutic tool for improving implantation and live birth rates from in-vitro fertilization and providing a means of attenuating pregnancy loss in recurrent pregnancy loss patients. An array of reports on the effects of PGS on embryo implantation and live birth rates has been made since its introduction, showing, variously, increases, decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The global prevalence of RM has exhibited an increasing trend, particularly due to the increasing age of pregnant women, and the availability of assisted reproductive technologies. 9 Moreover, epidemiological studies have revealed that pregnancies after a series of miscarriages have an increased risk of preterm birth, stillbirth, preeclampsia, and fetal growth restriction. 10 Several studies have implicated impaired EVT invasion in RM.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of RM has exhibited an increasing trend, particularly due to the increasing age of pregnant women, and the availability of assisted reproductive technologies. 9 Moreover, epidemiological studies have revealed that pregnancies after a series of miscarriages have an increased risk of preterm birth, stillbirth, preeclampsia, and fetal growth restriction. 10 Several studies have implicated impaired EVT invasion in RM.…”
Section: Introductionmentioning
confidence: 99%
“…Applied methods include, for instance, artificial insemination, in vitro fertilisation, and, in regard to animal species, cloning by somatic cell nuclear transfer. However, the pregnancy outcome suffers from limitations caused by the artificial treatments and in vitro culture of the germ cells and associated, altered patterns of gene expression [147][148][149][150]. This affects the health status of the newborn but also influences later periods of live.…”
Section: Laurasiatheriamentioning
confidence: 99%
“…Recurrent spontaneous abortion (RSA), a common complication of human pregnancy, refers to two or more abortions before the 20th gestational week. The incidence of RSA is approximately 1-5%, with an increasing trend in recent years (Go, Patel, & Cunningham, 2009;Tunc, Tanriverdi, Demirhan, Suleymanova, & Cetinel, 2016).…”
Section: Introductionmentioning
confidence: 99%